1997
DOI: 10.2307/3579626
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Transcriptional and Post-Transcriptional Expression of Gamma-Glutamylcysteine Synthetase by Diethyl Maleate

Abstract: Gamma-glutamylcysteine synthetase (gamma-GCS), also known as glutamate-cysteine ligase (EC 6.3.2.2), is the rate-limiting enzyme in the synthesis of glutathione (GSH). The gene GLCLC encodes the catalytic subunit while GLCLR encodes the regulatory subunit. Although it has been shown that GLCLC can respond to a variety of stresses by increased transcription, it is not known whether a similar response occurs for GLCLR. Nor is it known whether post-transcriptional regulation of either gene product is altered duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 20 publications
1
39
0
Order By: Relevance
“…In addition to increased gene transcription, DEM and 4-hydroxy-2-nonenal treatments have also been found to stabilize the GCLC mRNA (Sekhar et al, 1997a;Liu et al, 1998). The molecular mechanism of this effect remains unknown.…”
Section: Post-transcriptional Regulation Of Gclcmentioning
confidence: 99%
“…In addition to increased gene transcription, DEM and 4-hydroxy-2-nonenal treatments have also been found to stabilize the GCLC mRNA (Sekhar et al, 1997a;Liu et al, 1998). The molecular mechanism of this effect remains unknown.…”
Section: Post-transcriptional Regulation Of Gclcmentioning
confidence: 99%
“…Consistent with this effect we report here the induction of ␄-GCS-HS, the catalytic subunit of the rate limiting enzyme in GSH biosynthesis which determines a greater GSH biosynthetic capacity of mucosa 7 days after TNBS treatment. Since the gut is highly dependent on GSH synthesis (Martensson et al, 1990;Sido et al, 1998), the increase in ␄-GCS in mucosa from TNBS-treated rats can be interpreted as an adaptive response to control the consequences of the stress induced by TNBS as ␄-GCS-HS is known to be upregulated in response to divergent stressful conditions including oxidative stress or GSH depletion (Morales et al, , 1998Mulcahy et al, 1997;Rahman et al, 1996;Sekhar et al, 1997;Tian et al, 1997). However, despite almost normalization of mucosal GSH levels in the chronic phases of colitis (1-3 weeks) (Fig.…”
Section: Replenishment Of Glutathione Improves Mucosal Functionmentioning
confidence: 99%
“…Because of the critical role of GSH in protection against apoptosis, 19,21 we examined the effect of GSH depletion in the survival of hepatocytes following incubation with the SMases. Cells were first preincubated with DEM to cause a rapid elimination of cell GSH stores through GST catalysis, followed by BSO to prevent GSH recovery caused by the induction of ␄-GCS by DEM, 25 thus ensuring a sustained depletion of GSH levels during the course of incubation. As seen, although in hepatocytes not depleted of GSH levels hSMase caused a moderate cell killing after 12 hours of incubation, GSH depletion accelerated and increased the magnitude of cell killing by hSMase treatment (Fig.…”
Section: Effect Of Exogenous Smases On Hepatocellular Ceramide Levelsmentioning
confidence: 99%
“…The former catalyzes the rate-limiting step in de novo GSH synthesis, and has been shown to be up-regulated in multiple cell types in response to a diverse array of stimuli. [25][26][27][28][29][30] Recent studies in a human acute lymphoblastic cell line have indicated that NSMase is inhibited by GSH, whereas GSH depletion did not affect the activity of the acid pHoptimum ASMase, suggesting that cellular GSH selectively controls the activation of NSMase. 31 However, because the regulation of cellular GSH by either NSMase or ASMase has not been previously reported, we have examined the regulation of GSH and induction of oxidative stress in cultured rat hepatocytes incubated with exogenous SMases, including the commonly used Mg 2Ï© -dependent, neutral pH optimun bacterial SMase from Bacillus cereus (bSMase).…”
mentioning
confidence: 99%